2016
DOI: 10.1093/jscr/rjw188
|View full text |Cite
|
Sign up to set email alerts
|

Insulinoma or non-insulinoma pancreatogenous hypoglycemia? A diagnostic dilemma

Abstract: Insulinoma is the most common cause of endogenous hyperinsulinemic hypoglycemia in adults. An alternate etiology, non-insulinoma pancreatogenous hypoglycemia (NIPH), is rare. Clinically, NIPH is characterized by postprandial hyperinsulinemic hypoglycemia, negative 72-h fasts, negative preoperative localization studies for insulinoma and positive selective arterial calcium infusion tests. Histologically, diffuse islet hyperplasia with increased number and size of islet cells is present and confirms the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Insulinoma is an insulin-secreting tumor, which is the most common cause of EHH in adults [4]. The majority of cases are benign, solitary, small, and intrapancreatic [5].…”
Section: Discussionmentioning
confidence: 99%
“…Insulinoma is an insulin-secreting tumor, which is the most common cause of EHH in adults [4]. The majority of cases are benign, solitary, small, and intrapancreatic [5].…”
Section: Discussionmentioning
confidence: 99%
“…This method has high sensitivity varying from 72–100%, with most studies reporting a sentivity of 88–100% [29,3234]. In the diagnosis of endogenous hyperinsulinemic hypoglycemia it is important to differentiate insulinoma from the noninsulinoma pancreatogenous hypoglycemia syndrome(NIPHS), which is due to nesidioblastosis, as they are treated differently[35,196,205]. Unfortunately, the cross-sectional imaging may be negative in both, 68 Ga-DOTA-SSA PET/CT can give a false positive result in NIPHS suggesting insulinoma, and the selective calcium infusion with insulin gradients can be positive in both[35,205,206].…”
Section: Imaging In Specific Pannets With Special Featuresmentioning
confidence: 99%
“…In the diagnosis of endogenous hyperinsulinemic hypoglycemia it is important to differentiate insulinoma from the noninsulinoma pancreatogenous hypoglycemia syndrome(NIPHS), which is due to nesidioblastosis, as they are treated differently[35,196,205]. Unfortunately, the cross-sectional imaging may be negative in both, 68 Ga-DOTA-SSA PET/CT can give a false positive result in NIPHS suggesting insulinoma, and the selective calcium infusion with insulin gradients can be positive in both[35,205,206]. In a recent study [35] the results of the selective arterial calcium study with hepatic venous sampling for insulin(SACST) was reported to differentiate these two conditions using two criteria[a maximum increase in hepatic venous insulin concentration >91.5 or >263.5 ulU/mL] with 95% and 100% specificity, respectively.…”
Section: Imaging In Specific Pannets With Special Featuresmentioning
confidence: 99%
“…This disease leads to episodes of hypoglycemia during fasting and after physical activity. It is most commonly diagnosed in adults [16]. Historically the oldest criteria of insulinoma were described as Whipple's triad: symptoms consistent with hypoglycemia, a low plasma glucose concentration and relief of those symptoms after the plasma glucose level is raised [17].…”
Section: Hypercortisolismmentioning
confidence: 99%